PELATIHAN KOMPUTER MENGGUNAKAN APLIKASI MICROSOFT OFFICE UNTUK MENDUKUNG PROSES KEGIATAN BELAJAR MENGAJAR BAGI GURU MI SWASTA NW 2 BOROK’ TUMBUH KECAMATAN SURALAGA - Ahmad Fadli; Wardatul Jannah; Rosdiana Eka Juniyati; Hermansyah Hermansyah (KARYA: Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service activity aims to provide computer training using Microsoft Office applications to MIS NW 2 Borok Grow teachers, Suralaga District, East Lombok Regency to facilitate the process of teaching and learning activities and to improve teacher professionalism. This activity is also a form of coaching for teachers who are less able to operate computers even though in this digital era teachers are required to be able to apply computer technology, especially Microsoft office applications. This computer training is carried out for one month and is carried out in three stages. starting from the preparation stage, namely preparing all needs during the training, such as registering participants, preparing locations, and so on, the implementation stage, namely the delivery of material while accompanying the participants during the training activities, and the third stage, namely the evaluation stage. The results obtained from this training activity are that the participants who take part in the training are able to apply and master Microsoft Office applications, both Microsoft office word, excel, and PowerPoint properly and correctly.